KEMBALI KE NAGARI REKONSTRUKSI MASYARAKAT: ADAT BASANDI SYARAK, SYARAK BASANDI KITABULLAH (Studi Aplikasi dan Formulasi Perda Pemerintahan Sumatera Barat no 9 Tahun 2000) - Nelmaya, Nelmaya (Alhurriyah, 2010)
In the fact as we know that the regional autonomy has risen up the local identity. In West Sumatera, the identity of Nagari has been being risen up for reconstructing the local societies. The reconstruction of Nagari after the regional autonomy is being assisted in the regional regulation (Perda/ Peraturan Daerah) no 9 year of 2009. The regional regulation has been obtained by fast of the society in West Sumatera. That is why; on the year of 2006 there was a fantastic changes of the condition in West Sumatera that all of villages in all regencies have changed into a Nagari system, for the exception of Mentawai regency. Since until now, the Nagari systems that have been being created are 507 Nagari located in the regencies and 44 Nagari located in the city governmental. One of the most interesting issues about the changes system of Nagari is that the system is trying to build the societies of West Sumatera to be based on the philosophy of adat asandi syarak, syarak basandi kitabullah. However, this case has been being written in the regional regulation or Perda, that the system of Nagari governmental is being regarded as an effective system to reconstruct the societies which have a high cultural values and belief in God as stated on the format of philosophical system. Whereas, in fact that the identity of the Nagari societies in Minangkabau is based on the cultural philosophy. Then, the problem is about the philosophy of adat asandi syarak, syarak basandi kitabullah has been being applied and planned in the regulational regency as the same as with the ways of the formulation.